BHV-1 vaccine induces cross-protection against BHV-5 disease in cattle. - del Medico Zajac, Maria Paula (2006)
Protection against BHV-5 disease induced by inactivated BHV-1 or BHV-5 based vaccines was analysed. Two groups of calves were subcutaneously immunized with an inactivated BHV-1 or BHV-5 based vaccine. A third group was not vaccinated and used as control. In the post-vaccination period, we studied the humoral and cellular immune response resulting similar to both groups. The efficacy of the vaccines was tested after intranasal challenge of the calves with a virulent Argentinean BHV-5 isolate (A-663). All control animals developed neurological signs associated with BHV-5 infection and high levels of virus shedding. Calves immunized with the BHV-1 and BHV-5 inactivated vaccines were protected against BHV-5 disease. Our study provides evidence that strongly support the existence of cross-protection between BHV-1 and BHV-5 in calves. Even though this has already been suggested by previous works, this is the first time an exhaustive study of the immune response is performed and typical clinical BHV-5 meningoencephalitis signs are reproduced in an experimental BHV-5 challenge trial.